2016
DOI: 10.1002/jcla.21929
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Evaluation of Free Testosterone and Cortisol Immunoassays in Saliva as a Reliable Alternative to Serum in Sports Medicine

Abstract: The results of this study suggest that measurement of free testosterone and cortisol in saliva may be seen as a reliable alternative to their assessment in serum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 15 publications
3
24
2
Order By: Relevance
“…The present cortisol data corroborate earlier results: A positive association between salivary and circulating plasma/serum cortisol concentrations has been confirmed both at rest [2729] and following exercise [3033]. Further, we have shown that exercise induces a rise in plasma cortisol concentration immediately following exercise, a response which can be observed with a time lag in the salivary concentrations.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present cortisol data corroborate earlier results: A positive association between salivary and circulating plasma/serum cortisol concentrations has been confirmed both at rest [2729] and following exercise [3033]. Further, we have shown that exercise induces a rise in plasma cortisol concentration immediately following exercise, a response which can be observed with a time lag in the salivary concentrations.…”
Section: Discussionsupporting
confidence: 92%
“…The increases in pTest are consistent with previous reports [33], therefore suggesting that pTest may be used in SCI subgroups for the same diagnostic purposes as in the able-bodied population. The poor relationships between salivary and plasma testosterone also support previous research that questions the diagnostic value of salivary testosterone [35]; even though significant relationships have been shown between salivary and plasma/serum concentrations [27, 32], this was not replicated by others [33]. From a clinical perspective, the present study does not provide any evidence for testosterone deficiency in TETRA as previously reported [24].…”
Section: Discussionsupporting
confidence: 80%
“…[14,19,40] In contrast to the recent study of Lippi et al, [45] our data revealed a higher correlation between total serum to salivary testosterone (r = 0.605) than between free serum and salivary testosterone (r = 0.379). The results showed a correlation between serum total and free testosterone, urinary and salivary testosterone absolute concentrations, and time-matched data, which confirms the results of other studies also in combination with exercise.…”
Section: Hormone Quantificationcontrasting
confidence: 99%
“…This correction confirmed the results of the absolute concentrations, as testosterone augmented to the highest levels after 6 to 9 h and returned to baseline after removal of the hormone source. [45] Furthermore, the first multi-modal sensors are available for quantifying diverse steroid hormones in saliva fluid. The highest changes in total testosterone in serum were 211.4 ± 70.9 % and in urine 215 ± 101.5 %.…”
Section: Hormone Quantificationmentioning
confidence: 99%
See 1 more Smart Citation